2015
DOI: 10.1002/14651858.cd004794.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve water quality for preventing diarrhoea

Abstract: BackgroundDiarrhoea is a major cause of death and disease, especially among young children in low-income countries. In these settings, many infectious agents associated with diarrhoea are spread through water contaminated with faeces.In remote and low-income settings, source-based water quality improvement includes providing protected groundwater (springs, wells, and bore holes), or harvested rainwater as an alternative to surface sources (rivers and lakes). Point-of-use water quality improvement interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
169
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 250 publications
(179 citation statements)
references
References 174 publications
(153 reference statements)
7
169
1
2
Order By: Relevance
“…The majority (84 %) reported no incidents of digestive afflictions, including diarrhoea, in the family during the last 5 years. This was supported by an official statement by the Hobeni Clinic, although morbidity rates depend on self-reporting from the household members, which is known to produce substantial bias (Wolf et al, 2014;Clasen et al, 2015). Also, the microbiological water quality of 51 tested CCFSs showed contrasting results: none of the filtrate samples was free of coliform bacteria and 35 % even showed a deterioration in water quality (Fig.…”
Section: Field Surveymentioning
confidence: 66%
See 1 more Smart Citation
“…The majority (84 %) reported no incidents of digestive afflictions, including diarrhoea, in the family during the last 5 years. This was supported by an official statement by the Hobeni Clinic, although morbidity rates depend on self-reporting from the household members, which is known to produce substantial bias (Wolf et al, 2014;Clasen et al, 2015). Also, the microbiological water quality of 51 tested CCFSs showed contrasting results: none of the filtrate samples was free of coliform bacteria and 35 % even showed a deterioration in water quality (Fig.…”
Section: Field Surveymentioning
confidence: 66%
“…BSF with plastic housing was found to be as efficient as its concrete counterparts (Fabiszewski de Aceituno et al, 2012) and various researchers reported the success of locally produced, low-cost CWF Simonis and Basson, 2011;Mwabi et al, 2013). Recent reviews of reduction of diarrhoea by different POU interventions found filtration techniques superior to solar or chemical water disinfection (Wolf et al, 2014;Clasen et al, 2015). However, comparisons were blurred by a high risk of bias, since the data relied on self-reported diarrhoea and placebo POU interventions were missing.…”
Section: Introductionmentioning
confidence: 99%
“…However, these approaches can be difficult to maintain, and are often abandoned by users because of the taste of chlorinated water, the time required to treat the water, and the ongoing need to purchase water treatment materials [5][6][7][8]. Furthermore, the evidence supporting health benefits (such as reductions in rates of childhood diarrhea) of POU treatment has been disappointing, due in part to limited adherence to POU treatment [9], which itself is impacted by factors such as the taste of treated water and complexity of the treatment [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] While combined interventions would be expected to have a greater influence on multiple exposure pathways and thus a greater combined impact on health, there is limited evidence of additive benefits. 12 This may be due to poor uptake, inconsistent use or an incomplete understanding of relevant pathways. [8][9][10] In India, combining water and sanitation interventions may be more critical than just interrupting multiple transmission pathways for enteric infection; evidence suggests that household-level water access is integral to the use of improved sanitation in this context.…”
Section: Introductionmentioning
confidence: 99%